Fano-like chiroptical response in plasmonic heterodimer nanostructures. Issue 6 (29th January 2020) - Tian, Xiaorui; Sun, Shuli; Leong, Eunice Sok Ping; Zhu, Guodong; Teng, Jinghua; Zhang, Baile; Fang, Yurui; Ni, Weihai; Zhang, Chun-yang
Abstract : Fano resonance and Fano-like circular dichroism induced by electric–magnetic dipole coupling are observed in a simple heterodimer nanostructure. Abstract : Plasmonic chirality has attracted more and more attention recently due to the enhanced chiroptical response and its potential applications in biosensing. Plasmonic Fano resonance arises from the interference between a dark narrow resonance and a bright broad resonance, and it provides a new paradigm to control the plasmon mode interactions. Even though a strong circular dichroism (CD) effect has been predicted in chiral nanostructures with a Fano resonance, there are few experimental studies, and the correlation between the two effects is unclear. In this research, we investigate these two effects in plasmonic heterodimer nanorods in the same spectral range. We find that the heterodimer nanostructure exhibits a Fano-like resonance and Fano-like chiroptical response, both of which are correlated with the coupling between a super-radiant electric dipole and a sub-radiant magnetic dipole mode. Due to the interference nature of the Fano resonance, the Fano-like chiroptical response exhibits distinctively sharp features in a narrow spectral range. This Fano-like chiroptical response can be explained by a modified chiral molecule theory and a simplified coupled electric–magnetic dipole model. This research may provide new insight into the physics picture of plasmonic chirality and paves the way for the development of sensitive plasmonic sensors.